Two-Dimensional Thin Layer Chromatography-Bioautography Designed to Separate and Locate Metabolites with Antioxidant Activity Contained on Spirulina platensis - Margarita Cid-Hernández; Fernando Antonio López Dellamary-Toral; Luis Javier González-Ortiz; María Judith Sánchez-Peña; Fermín Paul Pacheco-Moisés (International Journal of Analytical Chemistry)
Spirulina platensis contains several biologically active compounds, some of them with antioxidant activity. Nevertheless, not all of these compounds have been identified to date. As a first step to achieving such identification, a methodology to perform two-dimensional thin layer chromatography bioautographies on silica gel thin layer chromatography plates was proposed. Starting with a reference binary system, 5 other binary systems were tested, in which the relative polarity was systematically increased. To further improve the separation behavior, a phase modifier (NH4OH) was used. The best separation results were obtained with the isopropyl alcohol/ethyl acetate/NH4OH ternary system. This experimental system allowed four well-resolved spots showing antioxidant activity as well as two additional areas with mixtures containing antioxidant compounds. Although the proposed methodology was designed with a specific application, it would be predictable that its field of use could be considerably greater, making the convenient modifications on the solvent polarity and “masking level” produced by the ammonium derivatives.